The Impact of Selected Regimens of Chronic HIV‐Antiretroviral Treatment on Glycemic Control Markers and Correlates: A Systematic Review and Meta‐Analysis Protocol - Mlindeli Gamede; Mbulelo Aubrey Sosibo; Nontobeko Gumede; Mluleki Luvuno (Health Science Reports)
ABSTRACT Background and Aim Diabetes mellitus is one of the leading causes of morbidity and mortality among non‐communicable diseases worldwide. The etiology of diabetes can be mainly attributed to factors such as genetic susceptibility, unhealthy diets, and chronic medications. Chronic medications such as HIV‐antiretrovirals (ARVs) have been previously associated with the risks of developing metabolic complications. Hence, this protocol outlines the process for conducting a systematic review to investigate the association between chronic ARV treatment and the onset of metabolic syndrome complications. Methodology and Analysis The studies included in the systematic review are selected according to the inclusion and exclusion criteria. These studies are searched using search engines or databases such as PUBMED, GOOGLE SCHOLAR, MEDLINE, ScienceDirect, and EMBASE DATABASE. The articles that remained after full article screening will be assessed for bias using the Downs and Black checklist, and the data will be extracted. Additionally, heterogeneity tests will be conducted using both Χ2 and I2 tests, meta‐analysis will be conducted using the Review Manager version 5.4 software (RevMan), and data will be presented in forest plots. Grading of Recommendations Assessment, Development, and Evaluation approach (GRADE) will be used to assess the strength of evidence in eligible reports. Dissemination and Registration The findings intend to give an insight into the ARVs as a risk factor for metabolic diseases and further elaborate on the regimen that possesses a high risk between the first and second regimens. This protocol has been registered on PROSPERO Database #CRD42024521322.